Multiple Choice Test Randomizer of ICT Department of Abra State Institute of Science and Technology - Guidang, Excel Philip (JPAIR Multidisciplinary Research, 2016)
Computer Aided Assessment (CAA) has been deployed in higher education to administer examinations in which the responses are electronically recorded, assessed, or both. CAA makes possible a detailed analysis of test results with minimal effort. It employed the descriptive and applied methods of research. A standardized research survey questionnaire was used. The study found out that 50.86% of the responses were computer aided, 43.43% were paper and pencil, 4.5% were board work and 1.4% was others. 45.14 of the responses were multiple choice, 22.29% were true or false, 17.14% were essay 14.86% were matching type and .57% were others. Test papers were physically distributed by the professors to students. HTML and CSS were used for GUI while PHP and MySQL for storing data. The Multiple Choice Test (MCT) software was evaluated usable. The study concludes that the students prefer computer-aided test as the delivery method of assessment. Moreover, students prefer multiple choice type of test especially when the assessment period is limited. The existing testing administration is manual. The combination of Hypertext Mark-up Language (HTML), Cascading Style Sheet (CSS), and Hypertext Pre-processor (PHP) and MySQL relational database management system is deemed effective in the development of a Multiple Choice Test Randomizer.